Family Determinants Causing Children Suffering From Wasting In Jambi City - Harahap, Huntari; Kusdiyah, Erny; Darmawan, Armaidi; Nur, Amrizal Muhammad (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2024)
Background: Toddlers who experience wasting will experience delayed growth and development if it occurs in the long term, a decrease in the immune system, are susceptible to infectious diseases, and can cause death if they experience severe wasting for a long time. This study aims to determine the family determinants of wasting in toddlers in Jambi City. Method: This study is a descriptive-analytical study with a Cross-Sectional research design. The study was conducted on 35 toddlers experiencing wasting who were treated at the Community Health Center in Jambi City and did not experience congenital abnormalities, were not undergoing steroid treatment, or did not experience other chronic diseases. The mothers of children suffering from wasting were given questionnaires, and interviews were conducted. Result: The results of the study showed that 45.7% were aged 31 to 40 years, 48.6% of mothers' education graduated from high school, 57.1% family income was less than 2 million, 82.9% of mothers did not work, 45.7% of drinking water sources came from PDAM water, the number of children in the family ≤ 2 children was 62.9%, and there was a relationship between maternal age, maternal education, family income, employment history, drinking water sources and number of children with wasting events (p-value <0.05). Conclusion: This study concludes that family determinants influence the incidence of wasting in toddlers in Jambi City. Keywords: Determinant; Family ; Todldlers; Wasting;